Teaching and Learning : The Role Played by Academic Boards : Final Report. - Vilkinas, Tricia; Peters, Margaret (Office for Learning and Teaching, 2012)
Final report of a Teaching Fellowship at the University of South Australia. Academic boards play a key role in the maintenance of quality and standards, and the provision of strategic leadership on academic issues. The purpose of this research project was to investigate the nature of the role provided at present to Australian universities through their academic boards. It aimed to determine what role academic boards play in their university; determine what aspects of academic governance academic boards deliver; identify the focus (external versus internal) of academic boards' activities; and determine how their effectiveness is measured and how effective they are. The Terms of Reference were used to determine what the academic boards say they should be doing and the Australian Universities Quality Agency (AUQA) reports were used to determine what they were seen to be doing.